Analysis of the Concepts of Physics in Detective Conan's Animation Film - Febri Syahrul Haj; Innita Fashihatul Qiroah; Binar Kurnia Prahani; Dwikoranto (Studies in Philosophy of Science and Education, 2021)
Detective Conan is an animated film genre originating from Japan. This study aims to analyze the concept of physics in several episodes in the film Detective Conan. The concept of physics in this film is contained in the phenomena that occur in it, so it is interesting to study. The type of research method used is the type of descriptive method. The research was carried out in the form of direct observation methods, namely watching animated episodes as well as data collection, literature studies and analysis of physics concepts to describe existing phenomena. Based on the results and discussion, it can be concluded that Detective Conan is a Japanese animated action genre film with the concept of the main character acting as a detective and is required to be able to solve all crime cases and puzzles so that they can be solved. Some of the physics concepts found in several episodes of Detective Conan are about Archimedes' law, Boyle's law, about temperature, perfect internal reflection, uniformly changing rectilinear motion and uniformly rectilinear motion, tyndall effect, electricity, dynamic electricity and up to parabolic motion. The study of the film Detective Conan is expected to be able to increase students' interest and abilities in learning physics. regarding temperature, perfect internal reflection, uniformly changing rectilinear motion and uniformly rectilinear motion, the Tyndall effect, electricity, dynamic electricity and up to parabolic motion. The study of the film Detective Conan is expected to be able to increase students' interest and abilities in learning physics. regarding temperature, perfect internal reflection, uniformly changing rectilinear motion and uniformly rectilinear motion, the Tyndall effect, electricity, dynamic electricity and up to parabolic motion. The study of the film Detective Conan is expected to be able to increase students' interest and abilities in learning physics.